PERENCANAAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA SEBAGAI IMPLEMENTASI KURIKULUM MERDEKA - Eka Putri Ningsih; Ika Fitriyati; Muhammad Agung Rokhimawan (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2023)
The independent program launched by the government is designed as an effort to improve the quality of education in Indonesia, following the decline caused by Covid-19. One of the new features of the independent program is the project to strengthen the profile of Pancasila “P5” students. P5 is implemented in the form of extracurricular activities to support intracurricular activities. Because it is  new, P5 requires careful planning so that schools have  clear images and implementation diagrams as a reference for P5 planning. With careful planning, it is  likely that P5 implementation  will also go smoothly. Madrasah Ibtidaiyah Negeri (MIN) 2 Bantul is one of the schools planning to implement an independent program in Bantul Regency, Yogyakarta Special Region province. Therefore, the purpose of this study is to describe P5's plans to undertake an independent research program. The study was conducted at MIN 2 Bantul. This research was designed using a qualitative method using a case study approach. Observation, interview and document data were used as research data. Once all the data is obtained, it is analyzed using the triangulation technique. The results of the research conducted at MIN 2 Bantul show that MIN 2 Bantul implements P5 planning by establishing a support team, identifying aspects and themes, designing  implementation schedules, designing module and design review. We hope  this study can become a reference for other studies related to P5 planning in the implementation of independent research programs.